(3JaSjQ ShQI GdENdGUs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje (B( (3bd gh Gddg GMO (B) (3Gdgh GdeWdb gh GdPi dGjchf ghjJg eSJaGOI ef ZjQg aeJi de jYJHQ ZjQg de jcf ghgh s
(3BNQgG (B:s
(3hEfg Ydi SHjd GdJYQjV hGdEjeGA Ydi LejY eG jJYdb HGdHMK Yf PGJg Edjg hGddg GdeMjW HCSQGQ cdGeg Je s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B449s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdJaSjQ hYdhe GdbQBfs